The Existence of Non-Star Hotel Businesses in Facing Government Efficiency Policies - Veronika A.S.M. Flora; Agustino L. F. Conterius Conterius; Najila Fukalang (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
This study explores the condition of non-star hotels in Kupang City in response to government efficiency policies using a qualitative approach with four hotel owners. The findings show that these hotels primarily serve small events and personal stays rather than government institutions. While the policy has no direct impact, it indirectly reduces income stability, with occupancy declining by about 50%. To cope, owners cut operational costs, and most employees often family members are paid below the minimum wage, sometimes with delayed payments. Government support is perceived as limited, leaving non-star hotels operating in a vulnerable condition.